النشاط السياسي لمصالي الحاج بين 1926 و 1936 وتشكل معالم التيار الثوري الاستقلالي الجزائري - بالأعرج, عبد الرحمن (جامعة الوادي - University of Eloued, 2022)
يهدف المقال إلى دراسة جوانب من تاريخ مصالي الحاج (1898-1974) بالتركيز على نشاطه السياسي الممتد من 1926 إلى غاية 1936 وهي المرحلة التي صبغت نضاله التحرري بالطابع الاستقلالي الثوري والمطالبة بالانفصال التام عن الكيان المستدمر. حيث تم تأسيس نجم شمال إفريقيا وانفصل الفكر الثوري الجزائري عن التيار الشيوعي الفرنسي، وأصبح له صبغة نضالية جزائرية خالصة. وخلال هذه المدة من النضال الاستقلالي تم توسيع القاعدة النضاليةلنجم شمال إفريقيا وصار له صدى دولي بعدما كان مقتصرا على فرنسا فقط. The article aims to study aspects of Messali al-Hadj’s history (1898- 1974) by focusing on his political activity that extended from 1926 to 1936, a stage that characterized his liberation struggle with a revolutionary independence and a demand for complete separation from the destroyed entity. Where the North African star was established, the Algerian revolutionary thought separated from the French communist current, and it became a purely Algerian struggle. During this period of the independence struggle, the North African star's struggle base was expanded and it had an international resonance after it was limited to France only.
مقال
Keywords: تاريخ الجزائر؛ التيار الاستقلالي؛ مصالي الحاج؛ نجم شمال إفريقيا؛ الشيوعية; Algeria's history; independence current; Mesali Hadj; North African star; communism